Return to the Sources: Revival of Traditional Nomads' Rights to Common Property Resources in the Code Pastoral of the Islamic Republic of Mauritania - Wabnitz, H. W. (2012)
Despite their economic importance, herders are generally neglected both by the governments of African countries and international donors. During the 1990s, nomadic livestock raising accounted for 75 percent of Mauritania's agricultural output, but received only 10 percent of the country's agricultural budget and donor support. In the past, there were few specific regulatory protections of nomadic economic activities. This article analyzes the content and impact of the Code Pastoral (enacted in 2000, effective in 2004) of the Islamic Republic of Mauritania. This law is a prime example of adapted, effective legislation. It recognizes the traditional common property regime practiced by nomads on pastoral lands classified as public domain and validates use-rights, a shift from exclusive ownership rights. The law is pragmatic, having been drafted by herders themselves to defend against the increasing encroachment of rangeland by farmers. It builds on traditional rules and Islamic law (sharia). The Code's 46 short articles define the law's objectives, lay down basic principles and rights through legal and customary notions, and provide for realistic, self-executory conflict resolution procedures. Appeal to state tribunals is envisaged as a last resort. The initial results indicate that the Code Pastoral has been a positive development for livestock raising in Mauritania.